Accuracy of both virtual and printed 3-dimensional models for volumetric measurement of alveolar clefts before grafting with alveolar bone compared with a validated algorithm: a preliminary investigation. Issue 1 (January 2017) - Kasaven, C.P.; McIntyre, G.T.; Mossey, P.A.
Abstract: Our objective was to assess the accuracy of virtual and printed 3-dimensional models derived from cone-beam computed tomographic (CT) scans to measure the volume of alveolar clefts before bone grafting. Fifteen subjects with unilateral cleft lip and palate had i-CAT cone-beam CT scans recorded at 0.2 mm voxel and sectioned transversely into slices 0.2 mm thick using i-CAT Vision. Volumes of alveolar clefts were calculated using first a validated algorithm; secondly, commercially-available virtual 3-dimensional model software; and finally 3-dimensional printed models, which were scanned with microCT and analysed using 3-dimensional software. For inter-observer reliability, a two-way mixed model intraclass correlation coefficient (ICC) was used to evaluate the reproducibility of identification of the cranial and caudal limits of the clefts among three observers. We used a Friedman test to assess the significance of differences among the methods, and probabilities of less than 0.05 were accepted as significant. Inter-observer reliability was almost perfect (ICC = 0.987). There were no significant differences among the three methods. Virtual and printed 3-dimensional models were as precise as the validated computer algorithm in the calculation of volumes of the alveolar cleft before bone grafting, but virtual 3-dimensional models were the most accurate with the smallest 95% CI and, subject to further investigation, could be a useful adjunct in clinical practice.